Electronic properties of lithium tantalate using Compton spectroscopy. (March 2020) - Joshi, Pooja K; Arora, G; Mali, D; Jangid, P K; Kumar, K; Ahuja, B L
Abstract: We have measured the electron momentum density (EMD) of LiTaO3 using 100 mCi 241 Am Compton spectrometer. The experimental Compton profile (CP) is compared with theoretical EMDs deduced using linear combination of atomic orbitals (LCAO) method with different exchange and correlation potentials namely PBE, PWGGA and VBH. On the basis of χ 2 fit (which scales goodness of fitting) and difference profiles between experimental and theoretical CPs, LCAO-PWGGA potential based CP is found close to experimental results. Electronic properties like energy bands and density of states of LiTaO3 using LCAO-PWGGA potential show a band gap of 4.85 eV of LiTaO3, thereby depicting its semiconductor nature with wide band gap. It is observed that upper valence band region is mainly dominated by 2p states of O and 5d states of Ta, although there is small contribution of 2s states of Li in this region.